Digital Green Carbon Trading Integrating Local Wisdom And Islamic Economy For Sustainable Development In Central Kalimantan - Akbar, Wahyu; Fahreza Setiawan, Rahmad; Fauzi Aseri, Akh; -, Muhaimin; Riza Hafizi, M. (Indonesian Journal of Islamic Economics and Business, 2025)
This article discusses the potential of digital green carbon trading in Central Kalimantan based on local wisdom and Islamic economic principles. Carbon dioxide (CO₂) emissions remain the leading cause of global warming, primarily driven by industrial and human activities. The study highlights how integrating digital technology, such as blockchain-based carbon registries and online trading platforms, can enhance transparency, accountability, and community participation in carbon markets. By empowering Dayak communities through digital access to carbon credit trading, environmental protection becomes an inclusive economic opportunity. This research uses a descriptive-qualitative method with a literature-based approach involving references related to carbon trading, digital economy transformation, Dayak local culture, and Islamic economics. The findings reveal that combining digital innovation, local wisdom, and sharia-based economic values offers a sustainable model for managing natural resources. This synergy not only reduces carbon emissions but also promotes the economic welfare of forest-dependent communities and strengthens digital local economies aligned with Maqasid al-Shariah and the Sustainable Development Goals (SDGs).